Peningkatan Penguasaan Materi Cahaya Melalui Penggunaan Model Pembelajaran Search, Solve, Create, And Share (SSCS) Pada Peserta Didik Kelas VIII - Saimima, Fadila; Kereh, Cicylia T.; Tuhurima, David (Pattimura University, 2022)
This study aims to determine the increase in the material mastery of class VIII students of SMP Al-Wathan Ambon on light material which is taught using the search, solve, create and share (SSCS) learning model. The sample in this study were students in class VIII2, totaling 22 people obtained using a purposive sampling method. Meanwhile, the instruments used to collect data were carried out using test and non-test instruments. Furthermore, to analyze the data that had been obtained, the achievement score formula and Gain test were used to determine the increase in mastery of the material that had been taught using the SSCS model. Based on the results of the research conducted, it can be seen that prior to being taught using the SSCS learning model students were categorized as failed by obtaining an average score of the initial test achievement obtained was 10.79. After being taught using the SSCS learning model, students get an increase in mastery of higher material. These results can be seen based on the average score of the students' final test, namely 82.67 and are in good and sufficient qualifications. In addition, there was an increase in class VIII2 students' mastery of the material on light. These results can be proven by the results of the Gain test which states that the average <g> value of students is 0.79 which is in high qualification. Therefore, it can be concluded that using the SSCS learning model can improve students' mastery of light in class VIII2 SMP Al-Wathan Ambon.